Offspring of parents with chronic pain: a systematic review and meta-analysis of pain, health, psychological, and family outcomes. Issue 11 (November 2015) - Higgins, Kristen S.; Birnie, Kathryn A.; Chambers, Christine T.; Wilson, Anna C.; Caes, Line; Clark, Alexander J.; Lynch, Mary; Stinson, Jennifer; Campbell-Yeo, Marsha
Abstract : Abstract: Offspring of parents with chronic pain may be at risk for poorer outcomes than offspring of healthy parents. The objective of this research was to provide a comprehensive mixed-methods systematic synthesis of all available research on outcomes in offspring of parents with chronic pain. A systematic search was conducted for published articles in English examining pain, health, psychological, or family outcomes in offspring of parents with chronic pain. Fifty-nine eligible articles were identified (31 population-based, 25 clinical, 3 qualitative), including offspring from birth to adulthood and parents with varying chronic pain diagnoses (eg, mixed pain samples, arthritis). Meta-analysis was used to synthesize the results from population-based and clinical studies, while meta-ethnography was used to synthesize the results of qualitative studies. Increased pain complaints were found in offspring of mothers and of fathers with chronic pain and when both parents had chronic pain. Newborns of mothers with chronic pain were more likely to have adverse birth outcomes, including low birthweight, preterm delivery, caesarian section, intensive care admission, and mortality. Offspring of parents with chronic pain had greater externalizing and internalizing problems and poorer social competence and family outcomes. No significant differences were found on teacher-reported externalizing problems. The meta-ethnography identified 6 key concepts (developing independence, developing compassion, learning about health and coping, missing out, emotional health, and struggles communicating with parents). Across study designs, offspring of parents with chronic pain had poorer outcomes than other offspring, although the meta-ethnography noted some constructive impact of having a parent with chronic pain. Abstract : Supplemental Digital Content is Available in the Text.This review and synthesis concludes that offspring of parents with chronic pain have poorer pain, health, psychological, and family outcomes than offspring of healthy parents.